An electronic questionnaire for liver assessment in congenital disorders of glycosylation (LeQCDG): A patient-centered study - Marques-da-Silva, Dorinda (2019)
Congenital disorders of glycosylation (CDG) are ultra-rare diseases showing a great phenotypic diversity ranging from mono-to multi-organ/multisystem involvement. Liver involvement, mostly nonprogressive, is often reported in CDG patients. The main objectives of this work were (1) to better understand liver involvement in CDG patients through a liver electronic questionnaire targeting CDG families (LeQCDG) and (2) to compare responses from LeQCDG participants with literature review regarding the prevalence of liver disease and the occurrence of liver symptoms in CDG patients. The network of patient advocacy groups, families and professionals (CDG & Allies – PPAIN) developed the LeQCDG by adapting validated published questionnaires. The LeQCDG was approved by an ethics committee, and the recruitment of patients and caregivers proceeded through social media platforms. Participants were asked to report past or present liver-related symptoms (e.g. hepatomegaly, liver fibrosis and cirrhosis) and laboratory results (e.g. biochemical and/ or radiological). From 11 December 2016 to 22 January 2017, 155 questionnaires were completed. Liver disease was present in 29.9% of CDG patients. Main symptoms reported included hepatomegaly, increased levels of serum transaminases, fibrosis, steatosis and cirrhosis. The data obtained in this online survey confirm findings from a recent literature review of 25 years of published evidence (r ¼ 0.927, P ¼ 0.02). Our questionnaire collected large amounts of meaningful, clinical and patient-oriented data in a short period of time without geographic limitations. Internet-based approaches are especially relevant in the context of ultra-rare diseases such as CDG.